Surgical Removal of a Canine Aortic Thromboembolism Secondary to Pancreatitis. (8th September 2015) - Narak, Jill; Graff, Emily C.; Saile, Katrin; Tillson, D. Michael
Abstract : A 7-year-old castrated male Pomeranian was evaluated on emergency for diagnostic work-up and treatment for acute nonpainful paraparesis. The neurologic examination suggested a L4-S3 myelopathy, but physical examination revealed lack of femoral pulses and rectal hypothermia, as well as a grade II/VI systolic heart murmur, so ischemic neuromyopathy was suspected. Clinicopathologic analysis revealed increased muscle enzymes and proteinuria. Abdominal ultrasonography confirmed aortic thromboembolism (ATE), and surgical histopathology diagnosed necrotizing pancreatitis. Surgical aortic thrombectomy was performed, and antithrombotic therapy was instituted. Pancreatitis was treated supportively. The dog was discharged to the owners after 10 days of hospitalization. Recheck examination 6 weeks after initial presentation revealed a normal neurologic examination and normal femoral pulses. The patient has had no further bouts of pancreatitis and remains neurologically normal 5 years after initial presentation. Canine ATE is relatively rare compared to the feline counterpart. Directed therapy for feline ATE is often not recommended, as underlying conditions are oftentimes ultimately fatal. Underlying etiologies for canine ATE include cardiovascular disease and endocrinopathies, but canine ATE secondary to pancreatitis has not yet been reported. Surgical removal of aortic thromboembolus should be considered as curative for pelvic limb dysfunction in the canine patient without a terminal underlying disease.